2016
DOI: 10.1186/s13098-016-0197-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a 6-month treatment with intragastric balloon on body composition and psychopathological profile in obese individuals with metabolic syndrome

Abstract: BackgroundThe aim of this study was to investigate the effects of a 6-month treatment with intragastric balloon (IGB) on body composition and depressive/anxiety symptoms in obese individuals with metabolic syndrome (MS).MethodsFifty patients (aged 18–50 years) with obesity and MS were selected for treatment with IGB for 6 months. Body composition was verified with dual-energy X-ray absorptiometry (DXA) at baseline and right after IGB removal. Anxiety/depressive symptoms were assessed with the Beck Depression I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 49 publications
(49 reference statements)
0
18
0
Order By: Relevance
“…This was the only study to use a clinical diagnosis and structured clinical assessment (a more reliable assessment of depression) instead of questionnaires. Furthermore, the only two studies on endoscopic bariatric procedures found a significant reduction in depression symptoms at three and 6‐month follow‐up …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This was the only study to use a clinical diagnosis and structured clinical assessment (a more reliable assessment of depression) instead of questionnaires. Furthermore, the only two studies on endoscopic bariatric procedures found a significant reduction in depression symptoms at three and 6‐month follow‐up …”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported on all three outcomes. Only two studies reported on endoscopic bariatric procedures, highlighting an urgent area of research and an important aim of this review . Therefore, results were discussed with reference to bariatric surgery and were not reflective of endoscopic bariatric procedures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations